2012
DOI: 10.4103/0971-6866.107984
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of the human ortholog gene Dicer1 in Pax2-Cre expression domain impairs orofacial development

Abstract: BACKGROUND:Orofacial clefts are common worldwide and result from insufficient growth and/or fusion during the genesis of the derivatives of the first pharyngeal arch and the frontonasal prominence. Recent studies in mice carrying conditional and tissue-specific deletions of the human ortholog Dicer1, an RNAse III family member, have highlighted its importance in cell survival, differentiation, proliferation, and morphogenesis. Nevertheless, information regarding Dicer1 and its dependent microRNAs (miRNAs) in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Indeed, the importance of miRNAs for craniofacial development in general, is supported by the severe craniofacial malformations seen in mouse embryos with a conditional deletion of Dicer in Wnt-1 expressing neural crest cells (Zehir et al ., 2010). Loss of Dicer expression in Pax2 -expressing cells also leads to craniofacial defects, including cleft palate and midfacial hypoplasia (Barritt et al ., 2012). We have thus conducted the current study to identify miRNAs that are expressed in the facial processes that contribute to the formation of the upper lip.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the importance of miRNAs for craniofacial development in general, is supported by the severe craniofacial malformations seen in mouse embryos with a conditional deletion of Dicer in Wnt-1 expressing neural crest cells (Zehir et al ., 2010). Loss of Dicer expression in Pax2 -expressing cells also leads to craniofacial defects, including cleft palate and midfacial hypoplasia (Barritt et al ., 2012). We have thus conducted the current study to identify miRNAs that are expressed in the facial processes that contribute to the formation of the upper lip.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional deletion of Dicer controlled by Pax2-Cre or Wnt1-Cre leads to perinatal death with severe craniofacial malformations in mice (Sheehy et al, 2010; Zehir et al, 2010; Nie et al, 2011; Barritt et al, 2012). Pax2 and Wnt1 expression is specific for cNC-derived mesenchyme from embryonic day (E) 7.5 and 8.5, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This may occur through miR-452, which is highly expressed in cNC-derived mesenchyme at E10.5 in the first pharyngeal arch and regulates Fgf8 and Dlx2 expression. In the Pax2-Cre; Dicer f / f mouse, a similarly large increase in apoptosis is present as well as a lower density of proliferating cells (Barritt et al, 2012). A Wnt1 -Cre; Dgcr8 f / f mouse exhibited a phenotype similar to that of the Dicer deletion and showed lower levels of pERK1/2, a kinase involved in another cell survival pathway (Chapnik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance, mutation of this cluster has been reported to cause cleft lip and palate (CL/P) by modulating the expression of Tbx1 , Tbx3 and Fgf10 , factors considered essential for midfacial development [27]. Barritt et al [28] identified complete palatal clefts when Dicer1 was ablated in the Pax2 - Cre / Dicer1 conditional knockout mice. In this model, knockout of Dicer1 did not affect early events in palatogenesis, such as cranial neural crest (CNC) migration to the first pharyngeal arch or the formation of palatal shelves, but fusion and mineralization of the palatal shelves were severely compromised.…”
Section: Introductionmentioning
confidence: 99%